Medición y predicción de la radiación solar global ultravioleta (0.295-0.385 μm) en condiciones de cielos claros y sin nubes (ING) - Wright, Jaime (2008)
Values of ultraviolet global solar radiation were measured with an ultraviolet radiometer and also predicted with an atmospheric spectral model. The values obtained with the atmospheric spectral model, which is physically based, were analyzed and compared with the experimental values measured in situ. The measurements were performed for different zenith angles under clear skies conditions in Heredia, Costa Rica. The necessary input data include latitude, altitude, surface albedo, Earth-Sun distance, as well as atmospheric characteristics: atmospheric turbidity, precipitable water and atmospheric ozone. The comparisons between the measured and predicted values gave satisfactory results.